Effects of cannabidiol (CBD) treatment on age-related cognitive decline in C57 mice - Mirza Agha, Behroo; Monteith, Merrin; Earl, Jarem; Ganske, Keona; Kaloa, Tina; McDonald, Kelan J.; Nixon, Abigail G.; Panjwani, Maleeha; Robinson, Danika; Rusnak, Valeria; Mohajerani, Majid H.; Kovalchuk, Igor; et al. (Frontiers in Aging Neuroscience, 2025)
Aging is associated with cognitive decline, and currently, there are no approved medications that can prevent these impairments. Recently, cannabinoids derived from Cannabis sativa have emerged as promising therapeutic compounds with neuroprotective, anti-inflammatory, and cognitive-enhancing properties. Despite their benefits, further research is needed to fully understand their efficacy across various conditions. This study investigates the effects of cannabidiol (CBD) on memory impairment and brain inflammation in aging mice. Fourteen-month-old C57 mice were administered CBD orally for 7 months and subsequently evaluated between 19 and 21 months of age using behavioral tasks that are sensitive to dysfunction of the perirhinal cortex, hippocampus, amygdala, and various brain regions that are crucial for motor control and coordination. The findings of this study indicate that CBD reduces inflammatory response in the brain and improves cognitive decline associated with aging.